Identification of demographic crises and evaluation of their intensity in the Kujawy region (Central Europe) in the 19th century - Drozd-Lipińska, Alicja; Bartczak, Arkadiusz; Krzemiński, Michał; Dziki, Tomasz (Anthropological Review, 2022)
Mortality crises are periods of unusually high mortality resulted from a combination of epidemic episodes, climatic phenomena, historical events and sociopolitical factors. The most pronounced setback in the methodology applied to analyse mortality rates of historical populations is the inability to establish their size.Reference publications do not provide unambiguous measures of the intensity and scale of mortality crisis periods. This problem was approached with the use of the Standardised Demographic Dynamics Rate (SDDR) whose value provides information about the condition of a population, disregarding the size of the group. Demographic crises were indicated and identified among the population living in the 19th century in central Poland in the rural parish. The analysis was based on data obtained from parish registers, made use of the measure expressing the ratio of the number of births to the number of deaths, without using the size of the group.Results obtained from the analysis of data were set against the information about events causing a sudden growth in mortality derived from the widely-accessible literature. Value of the Standardised Demographic Dynamics Rate (SDDR) provides information aboutthe condition of a population, disregarding the size of the group. Nevertheless, only by combining the statistically obtained data with the information derived from written records it is possible to attempt to answer the question of the possible root cause of a demographic crisis.